Factors affecting the work motivation of direct laborers at small and medium wood enterprises in Binh Duong region - Tran, Thị Hồng Ân; Nguyen, Minh Chân; Pham, Thị Quỳnh Như; Huynh, Thị Cẩm Duyên; Vu , Đức Quý; Ngo , Thị Phương Dung (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
Direct workers in the Binh Duong wood industry play a very important role thanks to their motivation to work in the context of increasing competition and high efficiency requirements. This study is based on the theory of planned behavior by Ajzen (1985), expanded with factors such as salary regime, work culture, colleague relations, recognition and professional development to overcome the limitations of TPB in predicting complex behavior. These factors promote positive attitudes, dedication and labor productivity, surveyed through a 5-point Likert scale and analyzed using the SPSS model. The research results provide an important basis for managers to build effective human resource policies, increase output and develop human resources in the Binh Duong wood industry in a sustainable direction.